First general report - Shortt, Edward; Nethersole, Olga, 1870-1951 (London : People's League of Health)
1922-05 1922 1920s 55 pages : illustrations League, accompanied by the Hon. Organiser at any time, to provide them with any medical information in possession of the Department which interested them. This would be of a standing character. July 15th, 1921. Establishment of a liaison Committee between the Ministry of Health and the People's League of Health, as suggested by the Chief Medical Officer of Health, Sir George Newman, consisting of the following members of the Medical Council :— Sir Bruce Bruce-Porter, K.B.E., C.M.G.. M.D. ; Sir Harry Baldwin, L.D.S., M.R.C.S. ; Dr. Buttar; Arthur Latham, F.R.C.P. ; and the original Founder and Hon. Organiser, Miss Olga Nethersole, with power and privileges of access at all times to the Ministry for conference, consultation and advice, and shall be known as Liaison Officers. HEALTH WEEK ACTIVITIES May, 1920. Participated in Health Week activities through our Branches. October, 1921. Participated in Health Week activities through our Branches, and supplied Tottenham Education Committee with Posters, Pamphlets and other literature. From a Leading Article in THE DAILY NEWS, May 4th 1922 :— VOCATION It was not difficult for Dr. G.H. Miles, in his address to the League of Health yesterday, to show the enormous economic waste involved in the vocational misfits arising out of our present haphazard methods of fitting the youth to the job. The advantage to the captains of industry of the careful scientific selection of recruits is plain to be seen ; we confess ourselves still more interested in the advantages to the workers themselves of guidance and selection made in the interest not primarily of the employers but of the employed. There is infinite pathos in the way in which masses of our youths — and maidens, too — have their vocations settled for them by blind invisible forces of which neither they nor their friends could give you in retrospect a coherent account. There are, of course, very many young people of character who know definitely what they want and manage to get it, but for each one of these there are a score who merely drift into what is handiest at the moment — and this not necessarily from the negligence of parents or guardians, who are genuinely perplexed and often quite helpless in the choice thrust upon them. "Vocational guidance, selection and training" not only "as a preventive of economic waste" but as the means to the self-fulfilment of each embryo citizen, should be regarded as one of the first and most binding duties of organised society. From The Right Hon. D. LLOYD GEORGE, Prime Minister, President of the Welsh National Branch of the League. "You cannot maintain an A1 Empire with a C3 population." D. Lloyd George 18 200/B/3/2/C693/1/71